2019
DOI: 10.21776/ub.jamal.2019.10.3.27
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Dewan Pengawas Sebagai Determinan Kinerja Sosial Bank Syariah

Abstract: Karakteristik Dewan Pengawas sebagai Determinan Kinerja Sosial Bank Syariah. Penelitian ini mencoba untuk menguji sejumlah karakteristik dewan pengawas dan pengaruhnya pada aspek kinerja sosial bank Syariah di Indonesia. Analisis regresi model random effect dipilih sebagai metode dengan Bank Umum Syariah 2012-2017 sebagai sampel. Penelitian ini menemukan bahwa keahlian keuangan dan frekuensi rapat mampu memacu kinerja sosial bank syariah. Hal ini terjadi karena kompetensi wajib dewan pengawas adalah bidang keu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 22 publications
3
11
0
Order By: Relevance
“…With "just wages", will minimize gaps be tween employees and surely increasing their prosperity. Dewindaru et al (2019) confirm that Islamic banks should hold the concept of a reasonable profit, just price, just wage and the welfare of society as main objectives. A consistent result is shown in multi ple regression analysis in which fairness and education simultaneously are examined its effect on public welfare.…”
Section: Comparison Of Maqasid Sharia Modelsmentioning
confidence: 82%
“…With "just wages", will minimize gaps be tween employees and surely increasing their prosperity. Dewindaru et al (2019) confirm that Islamic banks should hold the concept of a reasonable profit, just price, just wage and the welfare of society as main objectives. A consistent result is shown in multi ple regression analysis in which fairness and education simultaneously are examined its effect on public welfare.…”
Section: Comparison Of Maqasid Sharia Modelsmentioning
confidence: 82%
“…However, the results obtained are contradictory to the research by Firdaus (2017) and Alsartawi (2019) which concluded that the number of members has no impact on the performance of Islamic banks and recommends a more minimalist number of board members. This difference may occur given that most SSB members of Islamic banks in Indonesia are generally at a poor performance level, mainly due to the low fulfillment of the ideal characteristics of SSB such as the number of members, doctoral education, financial expertise, and the frequency of meetings as well as the presence of multi-task rule violation (Dewindaru et al, 2019). In addition, a smaller number of independent members will contribute to solving the problem of information asymmetry (Alsartawi, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The influence of SSB on public trust can also be found in the phenomenon of the excessive practice of multi-service SSB for Islamic banks in Indonesia. Study of Dewindaru et al (2019) found many cases of concurrent positions exceeding the maximum limit as that of suggested by POJK No. 30/POJK.05/2014, which shows a tendency for national Sharia banks to have SSB members from individual profiles who have experience holding many positions as members of Sharia banking SSB or individuals who are well known to the public.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Based on the framework and explanation of the criteria and sub-criteria above, then in principle, the findings of seven elements in the implementation of the real sector index are in line with the results of research on governance that must be applied in Islamic banks to increase public confidence. The results of the study stated that Islamic governance performance and public trust of Islamic banks need to be improved (Dewindaru et al, 2019). Islamic Corporate Governance is the most important point to reduce fraud, speculation, insider trading, and other moral hazards (Alzahrani, 2019).…”
Section: Resultsmentioning
confidence: 99%